Inteligentne tekstilije: navodila za laboratorijske vaje - Šauperl, Olivera; Volmajer Valh, Julija (University of Maribor Press, 2017)
Intelligent Textiles: Instructions for Laboratory Work. Nowadays, intelligent textiles are indispensable part of different clothing systems. As such they are able to detect and to respond to internal and external stimuli with great ability to be adapted to different factors. Materials with integrated microcapsules, photovoltaic cells, as well as those with built-in carbon, or optical memory wires, together with hydrogels and aerogels have a prominent role in a new age clothing systems. All these concepts are therefore, included within this exercises where students through practical work will recognize the importance and practical value of some intelligent systems.